Lysine deacetylase inhibition promotes relaxation of arterial tone and C‐terminal acetylation of HSPB6 (Hsp20) in vascular smooth muscle cells. Issue 6 (7th November 2013) - Chen, Aiqing; Karolczak‐Bayatti, Magdalena; Sweeney, Michèle; Treumann, Achim; Morrissey, Kelly; Ulrich, Scott M.; Nicholas Europe‐Finner, G.; Taggart, Michael J.
Abstract: There is increasing interest in establishing the roles that lysine acetylation of non nuclear proteins may exert in modulating cell function. Lysine deacetylase 8 (KDAC8), for example, has been suggested to interact with α ‐actin and control the differentiation of smooth muscle cells. However, a direct role of smooth muscle non nuclear protein acetylation in regulating tone is unresolved. We sought to define the actions of two separate KDAC inhibitors on arterial tone and identify filament‐interacting protein targets of acetylation and association with KDAC8. Compound 2 (a specific KDAC8 inhibitor) or Trichostatin A (TSA, a broad‐spectrum KDAC inhibitor) inhibited rat arterial contractions induced by phenylephrine (PE) or high potassium solution. In contrast to the predominantly nuclear localization of KDAC1 and KDAC2, KDAC8 was positioned in extranuclear areas of native vascular smooth muscle cells. Several filament‐associated proteins identified as putative acetylation targets colocalized with KDAC8 by immunoprecipitation (IP): cortactin, α ‐actin, tropomyosin, HSPB1 (Hsp27) and HSPB6 (Hsp20). Use of anti‐acetylated lysine antibodies showed that KDAC inhibition increased acetylation of each protein. A custom‐made antibody targeting the C‐terminal acetylated lysine of human HSPB6 identified this as a novel target of acetylation that was increased by KDAC inhibition. HSPB6 phosphorylation, a known vasodilatory modification, was concomitantly increased. Interrogation of publicly available mass spectrometry data identified 50 other proteins with an acetylated C‐terminal lysine. These novel data, in alliance with other recent studies, alert us to the importance of elucidating the mechanistic links between changes in myofilament‐associated protein acetylation, in conjunction with other posttranslational modifications, and the regulation of arterial tone. Abstract : e00127 Abstract : There is increasing interest in establishing the roles that lysine acetylation of non nuclear proteins may exert in modulating cell function. We report that inhibition of lysine deacetylase activity non‐epigenetically relaxes arterial tone and introduces site‐specific changes in lysine acetylation of the myofilament interacting protein HSPB6. These data contribute to an increasing appreciation that myofilament‐associated protein acetylation is an important regulator of arterial tone.